KHOREZM EXPEDITION SCHOLARS' CONTRIBUTION TO THE STUDY OF MEDIEVAL FORTRESSES: A HISTORIOGRAPHICAL ANALYSIS - Mirzayeva Munira Ilxomovna (International Journal of Literature and Language Studies, 2026)
This article analyzes the stages of studying medieval fortresses by members of the Khorezm Archaeological-Ethnographic Expedition of the 20th century, examines their scientific legacy, and assesses its significance for contemporary archaeological research. The study traces the development of fortress archaeology in the Khorezm oasis from the expedition's foundational work in the 1930s through its systematic investigations under the leadership of S.P. Tolstov. Special attention is given to the classification of fortresses according to chronological and functional criteria, the architectural and engineering innovations documented by expedition members, and the ongoing scholarly debates that have emerged from their findings. The research draws upon published expedition reports, monographs, and articles by expedition members, as well as subsequent scholarship that has built upon and, in some cases, refined their conclusions. The study employs historical-comparative methods and systematization of archaeological materials to demonstrate how the expedition's legacy continues to inform modern archaeological practice in the region.